Improving the interlaminar properties of polymer composites using a situ accumulation method to construct the multi-scale reinforcement of carbon nanofibers/carbon fibers. (May 2015) - Ma, Lin; Wu, Lixin; Cheng, Xiuyan; Zhuo, Dongxian; Weng, Zixiang; Wang, Rui
Abstract: A novel method was developed to realize the situ accumulation of carbon nanofibers (CNFs) in the carbon fiber reinforced polymer composites (CFRPs) to construct the multi-scale reinforcement for improving the interlaminar properties. In this method, the prepreg was sealed by the nanomicroporous nylon membrane, and the excess resin was extracted from the prepreg by the vacuum-assisted method. It was found that the use of nylon membrane resulted in effective CNFs accumulation, especially in the interlayer by scanning electron microscopy. Short-beam strength tests and the end-notched flexure tests were conducted respectively to evaluate the interlaminar properties of CFRPs under shear loading. The results indicated that the interlaminar shear strength (ILSS) and the Mode II interlaminar fracture toughness (GIIC ) of CFRPs made by the filtering membrane-assisted method remarkably increased compared with those prepared without using filtering membrane.